An Unnoticed Hero of Pakistan's Independence Movement; A Case of Biography Mr.Naseem Hijazi - Qamar Uddin Zia Ghaznavi (CSRC Publishing, 2021)
Purpose: In this article, Mr. Naseem Hijazi, a lesser-known hero of the Pakistan Movement, is highlighted. The primary purpose of this paper is to expose the hidden aspects of Mr. Naseem Hijazi's life. He was a well-known novelist and writer, as well as a freedom fighter. He was a member of the Pakistan Movement, but few people were aware of his involvement. He was a devoted Muslim and a firm believer in Islam. This research paper investigates and analyses the life of Naseem Hijazi to get a complete image of him.